The Effects of Short-Time Delayed Sealing on Fermentation, Aerobic Stability and Chemical Composition on Maize Silages - Natália Nunes de Melo; Paula de Almeida Carvalho-Estrada; Queila Gouveia Tavares; Lucelia de Moura Pereira; Gabriela Leticia Delai Vigne; Douglas Messias Lamounier Camargo Rezende; Patrick Schmidt (Agronomy, 2023)
Despite the efforts to improve the methodological standards of silage trials, many factors that can influence the results of lab-scale studies need to be better understood. This study aimed to determine the effects of short-time delayed sealing and inoculation with a blend of Lentilactobacillus buchneri and Lactiplantibacillus plantarum on fermentation, aerobic stability, and chemical composition of silages. Whole-crop maize was treated with or without a commercial inoculant and ensiled (29.3% dry matter) for 55 days in 8.8 L PVC silos that were sealed immediately (up to 30 min delay) or after a delay (90, 150, or 210 min between chopping and sealing) with five replicates each. The increasing air exposure before sealing increased fermentation losses and reduced silage nutritional value. Crude protein and ash were significantly affected by inoculation, with control treatments showing higher ash and lower protein values. Lignin, neutral detergent fiber, and acid detergent fiber were only affected by the delay period. The longer the sealing delay, the higher the gas production, and the lower the starch values and lactic acid content observed in samples. Inoculation was inefficient in reducing total dry matter losses, but it increased aerobic stability, acetic acid, and ethanol contents of silages and reduced effluent loss. Control silages had higher total dry matter loss during the aerobic exposure than inoculated silages. The results confirmed that the delay periods tested were long enough to negatively interfere with the chemical composition of silages, especially the fibrous fraction content.